OP0081 PAN-PPAR agonist IVA337 is effective in the prevention of experimental lung fibrosis and pulmonary hypertension. (15th June 2017) - Avouac, J; Konstantinova, I; Guignabert, C; Sadoine, J; Thomas, G; Pezet, S; Cauvet, A; Tu, L; Luccarini, JM; Junien, JL; Broqua, P; Allanore, Y
Abstract : Background: Peroxisome proliferator-activated receptors (PPARs) are nuclear receptors known to modulate fibrosis. The pan-PPAR agonist IVA337 recently demonstrated efficacy in prevention and treatment of experimental skin fibrosis (1). Objectives: Our objective was to evaluate the antifibrotic effects of IVA337 in preclinical mouse models of pulmonary fibrosis and related pulmonary hypertension (PH). Methods: IVA337 has been evaluated in the mouse model of bleomycin-induced pulmonary fibrosis and in Fra-2 transgenic mice, this latter being characterized by non-specific interstitial pneumonia and severe vascular remodeling of pulmonary arteries leading to PH. Mice received 2 doses of IVA337 (30 mg/kg or 100 mg/kg) or vehicle administered by daily oral gavage up to 4 weeks. Results: Both 30 mg/kg and 100 mg/kg doses of IVA337 were well tolerated in all mouse models. IVA337 demonstrated at a dose of 100 mg/kg a marked protection from the development of lung fibrosis induced by bleomycin compared to mice receiving 30 mg/kg of IVA337 or vehicle. Indeed, IVA337 (100 mg/kg) strongly reduced by 61% and 28% tissue density on histological measurements and total lung hydroxyproline concentrations, respectively, as compared to vehicle. IVA337 at 100 mg/kg also significantly decreased col1, col3 and fibronectin in lesional lungs. Similarly, Fra-2 transgenic mice treated with 100 mg/kg of IVA337 displayed reduced lung density (20% vs. vehicle) and significant increase of functional residual capacity (30% vs. vehicle) when assessed by chest micro-CT imaging. These results were emphasized by a 50% reduction of the Ascroft fibrosis score (Figure 1 A) and by a 48% reduction of hydroxyproline concentrations upon IVA337 (100 mg/kg) compared to vehicle treated mice. Successful targeting of the TGF-b signaling axis was observed in both mouse models upon treatment with 100 mg/kg of IVA337. 100 mg/kg IVA337 also significantly reduced T cell and B cell infiltration in lesional lungs of Fra-2 transgenic mice. Regarding vessel remodeling and related pulmonary hypertension, treatment with 100 mg/kg of IVA337 led to a substantial attenuation of right ventricular systolic pressure and right ventricular hypertrophy compared to mice receiving the vehicle (Figure 1 B and 1C). Furthermore, IVA337 given at 100 mg/kg markedly reduced medial wall thickness (Figure 1 D) and the number of muscularized distal pulmonary arteries. In vitro in primary human lung fibroblasts, IVA337 inhibited in a dose-dependent manner TGFβ-mediated fibroblasts to myofibroblasts transition and PDGF-mediated proliferation. Conclusions: We demonstrate that treatment with 100 mg/kg IVA337 prevents lung fibrosis in two complementary animal models and substantially attenuates PH in the Fra-2 mouse model. These findings confirm that the pan-PPAR agonist IVA337 is an appealing therapeutic candidate for systemic sclerosis both, for skin and key cardiovascular complications. References: Ruzehaji et al, Ann Rheum Dis 2016;75(12):2175–2183. Disclosure of Interest: J. Avouac: None declared, I. Konstantinova Employee of: INVENTIVA, C. Guignabert: None declared, J. Sadoine: None declared, G. Thomas: None declared, S. Pezet: None declared, A. Cauvet: None declared, L. Tu: None declared, J. M. Luccarini Employee of: INVENTIVA, J. L. Junien Consultant for: INVENTIVA, P. Broqua Employee of: INVENTIVA, Y. Allanore Grant/research support from: Inventiva